2012
DOI: 10.5455/vetworld.2012.603-608
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the duration of immunity induced in cattle after natural FMD infection and post vaccination with bivalent oil vaccine

Abstract: Aim: To detect the proper time for vaccination of infected calves after the onset of clinical signs and revaccination for previously vaccinated animals with bivalent FMD montanide ISA206 inactivated vaccine. Materials and Methods: Twenty calves naturally infected with foot and mouth disease (FMD) showing clinical signs represented by lesions on the tongue, buccal mucosa and feet. Samples were collected from these calves including tongue epithelial and oropharyngeal fluid (OP). The causative virus was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…The isolate was confirmed as FMDV serotype SAT2 using CFT; ELISA and PCR (Table -1). The use of such techniques for isolation; identification and typing of FMDV were recommended by [26,28,10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolate was confirmed as FMDV serotype SAT2 using CFT; ELISA and PCR (Table -1). The use of such techniques for isolation; identification and typing of FMDV were recommended by [26,28,10].…”
Section: Resultsmentioning
confidence: 99%
“…Veronal buffer (8 ml) was added to the homogenized tissues, and chloroform added to the mixture, followed by centrifugation at 7000 rpm for 10 min at 4°C. The supernatant was collected and tested for FMDV presence in tissue culture and mice [10].…”
Section: Tongue Epithelialmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval of antibody response in experimentally infected cattle with FMDV persisted for duration of 40 weeks. 47 Mohan et al 48 These findings showed that only IgA antibodies detected at late stages of infection were specific to genuine mucosal responses.…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…A rise in serum antibody titer can be detected around 28 days and remains at protective levels thereafter. The interval of antibody response in experimentally infected cattle with FMDV persisted for duration of 40 weeks …”
Section: Introductionmentioning
confidence: 99%